Application of Vendor Managed Inventory Cooperation Model to Encourage Distribution of Products in Ud. Sari Jaya - Andary Asvaroza Munita; Muhammad Kholil; Galih Raka Siwi; Adizty Suparno (Institute for Research on Innovation and Industrial System (IRIS), 2020)
UD. Sari Jaya is a home industry that produces cassava and other tubers into chips. Cassava chips are the main product because of their high level of consumer interest in the product compared to others. The Problems faced by UD. Sari Jaya is that they are unable to meet the market demand more effectively. In the process of providing the needs, UD. Sari Jaya often performs several deliveries to each Stall caused by the lack of product availability at Stall, causing demand to be unfulfilled. The number of Retailers to be served, the lack of information on needs is one of the obstacles in the process of inventory replenishment. Vendor Managed Inventory (VMI) is one of the Collaboration Model in the supply chain between producers and retailers where collaboration is expected to make arrangements regarding the number of lot sizes order as well as the frequency of deliveries to each Stall with a minimum total cost, by thus UD. Sari Jaya can have good control in the process of fulfilling the needs of this Cassava Chips.